Outsourcing and offshoring of business services: How important is ICT? - Laura Abramovsky; Rachel Griffith (Institute for Fiscal Studies (IFS), 2005)
This paper considers the impact that technology has on firms' choices over organisational form, in particular whether to produce inhouse or outsource and offshore services, and firms' decision over the location of activity. Technology reduces the transaction and adjustment costs of moving activity outside the firm and of carrying out at greater geographic distance. We find that more technology intensive firms purchase a greater amount of services on the market and purchase more offshore than less technologically intensive firms.
Keywords: D21; F23; L23; 330; Outsourcing; oshoring; ICT; business services; Outsourcing; Informationstechnik; Auslandsverlagerung